Structure and Stability of B10N14: Cages, Sheets, and Rings - Melanie Walker; Kelvin Jones; DaiQuan Noble; Marquavias Walker; Douglas L. Strout (Journal of Chemistry)
Boron nitride is a material similar to carbon in its ability to adopt numerous molecular forms, including two-dimensional sheets and three-dimensional cages and nanotubes. Boron nitride single molecules, such as B12N12, have isomeric forms that include rings and sheets, as well as cage forms analogous and isoelectronic to the carbon fullerenes. Such cages tend to be composed of squares and hexagons to allow perfect alternation of boron and nitrogen atoms, which is possible because of the 1 : 1 ratio of boron-to-nitrogen atoms. What about molecules in which this 1 : 1 ratio does not apply? In the current study, theoretical calculations are carried out on molecules of B10N14 to determine energetically favorable isomers. Density functional theory is used in conjunction with Dunning basis sets. Cage, sheet, and ring isomers are considered. Energetic trends are calculated and discussed, in comparison to comparable studies on B12N12.